Review and evaluation of estuarine biotic indices to assess benthic condition - Pinto, Rute (2008)
Recently there has been a growing interest and need for sound and robust ecological indices to evaluate ecosystem status and condition, mainly under the scope of the Water Framework Directive implementation. Although the conceptual basis for each index may rely on different assumptions and parameters, they share a common goal: to provide a useful tool that can be used in assessing the system's health and that could be applied in decision making. This paper focuses mainly on benthic community-based, biotic indices. We supply a general overview of several indices premises and assumptions as well as their main advantages and disadvantages. Furthermore, an illustrative example is provided of a straightforward application of benthic index of biotic integrity and benthic condition index. As a reference, their performance is compared to the Portuguese-benthic assessment tool. Limitations of the tested indices are discussed in context of the Mondego estuary (Portugal) case study.